EVALUATION OF THE EFFECT OF INTRATESTICULAR MANNITOL IN GUINEA PIGS (CAVIA PORCELLUS) AND ITS INFLUENCE ON ZOOTECHNICAL PARAMETERS - FABIÁN BAYAS-CHILENO; FRANKLIN FUENTES-GALEAS; RIVELIÑO RAMÓN-CURAY; JONNATHAN ARIAS-REAL; SANDRA ROBALINO-NIETO (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objective: Chemical castration is emerging as an effective alternative to surgical sterilization, overcoming its disadvantages and allowing large-scale sterilization in a short period of time. The objective of this study was to evaluate the effect of intratesticular mannitol injection in guinea pigs and its influence on zootechnical parameters. Methods: A total of 0.1 mL of 20% mannitol was administered intratesticular, forming three treatment groups: Surgically castrated guinea pigs (T0), one dose of mannitol (T1), and two doses of mannitol, 15 days apart (T2), over a period of 8 weeks. Variables such as body weight, weight gain, feed intake, feed conversion, and testicular morphometry were evaluated. Fifty-five days post-injection, testicular biopsies were taken for histological analysis. Results: Guinea pigs in treatments T2 and T1 had higher final live weights compared to T0, with weekly gains of 39.33 g, 28.73 g, and 22.57 g, respectively. Feed intake and feed conversion were more efficient in T1 and T2. No complications or adverse effects were observed, although severe testicular atrophy was evident in T2. Histological findings indicated that mannitol negatively affects spermatogenesis and steroidogenesis. Conclusion: Intratesticular mannitol represents a safe and effective option for the sterilization of male guinea pigs, allowing for the maintenance of zootechnical performance and avoiding post-operative complications associated with surgical castration.